Investigating the Effect of Surface Properties on Ice Scaling in Eutectic Freeze Crystallization - Motsepe, Lerato (Department of Chemical Engineering, 2021)
Eutectic Freeze Crystallization (EFC) is an innovative technology that can be applied to treat reverse osmosis (RO) waste streams (brines), to produce pure salt and water. Scaling of the heat exchanger (HX) surface by both ice and salt is currently one of the major drawbacks in the industrial implementation of EFC. At present scaling is controlled by the use of mechanical scraping, which is susceptible to mechanical breakdown, thus reducing the overall process efficiency. Previous studies have shown that lower surface energy materials delay the onset of freezing, and that smooth surfaces reduce nucleation and adhesion sites, thereby reducing the probability of scale formation. Therefore, this study aimed to investigate how the HX surface properties affect ice scaling in EFC, without the influence of mechanical scraping. Copper, Aluminium, Stainless Steel 316 and Brass were the selected HX materials. Ice scaling on the HX materials was investigated using a near eutectic 4 wt.% Na2SO4 aqueous solution, in a crystallization test cell uniquely designed to mimic the region near the HX wall of a crystallizer. The Differential Interference Contrast (DIC) technique was used to study the formation of the initial ice scale layer on the HX material used in the test cell. This method of observation was effective, asfor the first time in a continuous system, the crystallization of the initial ice scale layer was observable in-situ and in real-time. Therefore, with this method, it was possible to investigate the evolution of the predominantscaling modes(nucleation and growth), which differed for the different HX surfaces. The difference was proposed to be due to their distinct surface free energies and surface topographies. The effect of surface free energy and topography on the scaling induction time was investigated while operating at similar heat fluxes (similar cooling rates) for all the metals. The scaling induction time decreased with an increase in the surface free energy, with the Aluminium as an outlier. The recorded scaling induction times for Brass, primary-SS316 and Copper were 92.54, 70.95 and 54.06 min, respectively. Aluminium recorded the longestscaling induction time of 134.74 min. Both the polytetrafluoroethylene (PTFE) coated-SS316 and the primary-SS316 HX surface were used to investigate further the effect of surface free energy on the scaling induction time. The PTFE-coated-SS316 was found to increase the scaling induction times 2.79-fold at a coolant temperature of -15°C, compared to that of the primary-SS316. However, at -20°C and -25°C, the scaling induction times on both surfaces were comparable, which indicated that the benefit of using a low surface free energy material was limited by the cooling rate of the system. It was also found that the scaling induction times were shorter when using a rough-SS316 HX plate, compared to the primary-SS316, because of the larger surface area available for heat transfer. The end of the scaling induction time was characterised by the heterogeneous nucleation and subsequent growth of the ice on the HX surfaces. There was no direct correlation between the HX surface free energy and the nucleation and growth rates. This was because the Brass, Aluminium, SS316 and Copper plates all consist of different surface topographies which also influenced the nucleation and growth rates. However, the nucleation rates consistently increased when the scaling induction times were longer, regardless of the HX material used. The presence of deep sharp crevices on the primary-SS316 also enhanced nucleation rates. These deep sharp crevices created regions of high local supersaturation, where heterogenous nucleation predominated. It was, therefore, reasonable to conclude that the ice scaling induction time was increased by using smooth materials and those of lower surface free energy. The scaling mode was dependent on the surface topography and length of the ice scaling induction time, as longer ice scaling induction times resulted in heterogenous nucleation dominated scaling mode and vice versa. Materials that had a low surface free energy and were smooth minimised the nucleation rate, resulting in a reduced overall scaling rate.